The satisfaction with love life scale - Félix Neto (2005)
The purpose of this article was to develop the Satisfaction With Love Life Scale (SWLLS). Scores from the SWLLS have favorable psychometric properties. Evidence based on relations to other variables was examined. Suggestions concerning the use of the SWLLS for research and clinical purposes are offered.